Local Waveforms Analysis to Estimate the Fault Plane of May 2008 Sumatra Earthquakes: Bagus Jaya Santosa, Bintoro Anang Subagyo - Bagus Jaya Santosa Bagus Jaya Santosa; Bintoro Anang Subagyo Bintoro Anang Subagyo (Jurnal Fisika dan Aplikasinya, 2017)
Five earthquakes source parameters in Sumatra have been estimated that occurred on May 3rd, 13th , 18-20th 2008, which earthquakes magnitude was over 5.4 Mw. To determine the earthquakes source parameters, we used three components local waveform. The seismogram data are inverted to achieve the earthquake source parameters. To investigate the depths of earthquakes, the determination used the highest value of variance reduction of waveform analysis. To identify the fault plane of the earthquakes, the H-C method is used. The research calculates also the length and width of the Fault planes.